Developing Assumptions for the Tram Noise Attenuation Passive System Using the Noise Maps Analysis Method - NOWAKOWSKI, Tomasz; FIRLIK, Bartosz; STAŚKIEWICZ, Tomasz (Archives of Acoustics, 2019)
The paper presents experimental research carried out to determine the possible actions to reduce the noise generated by trams in a highly urbanised area. A few design strategies affecting tram ride quality have been presented – especially in the aspect of the acoustic phenomena. Main sources of the noise in trams were characterised. The paper includes selected results of comprehensive studies of tram noise in the pass-by test based on the authors’ research methodology. The tests were carried out on various types of trams to recognise the acoustic phenomena characteristic for the rolling stock in a selected tram system. The results of the measurements were analysed both in the field of amplitudes based on noise maps and in respect to frequencies based on noise spectra. The results indicated the rolling noise as important issue demanding taking some actions in order to reduce its level. In this area, elements for the application of individual attenuation solutions, i.e. at the source and during propagation, were presented. The results of the measurements were used as input data to the assumptions of the noise attenuation passive system, which was the final outcome of the study. Dedicated external dampers were used in the case of wheel and rail pairs, where the dominant power of the noise is emitted. The acoustic properties of the bogie area and the bogie side covers were redeveloped to hamper the noise propagation, which is a novel application. The presented results indicate measurable benefits from the applied solutions on the tram noise reduction.